A ludomatemática na educação de estudantes surdos(as) na perspectiva inclusiva - Silva, José Affonso Tavares (2019)
The current dissertation presents discussions regarding three areas - playfulness, math education and education of the deaf. The general objective of this research is analysing possible implications of the use of playful activities in the teaching of mathematics for deaf students included in classes in the early years of primary education in a state school of Aracaju- SE. The subject of Mathematics, considered one of the most important for the social and academic development of the person has undergone substantial changes in its teaching, mainly with the deaf students inclusion in the context of the classroom in which it has made the teacher rethink how and for whom they are teaching. In this juncture, assuming that research of qualitative approach, it was held a case study in a institution considered with the major number of deaf people included in the state of Sergipe. Among the data collection instruments, it were held: questionnaire to 3 teachers who work in the early years of the aforemented institution; the observation of teacher‟s practice of year 4 class “A” and an interview with the teacher who teachs this class. In order to give theoretical subsidies to the survey, it was supported by the following references: Lorenzato (2012); Kishimoto (2010), who argue over games. Goldfeld (2003) e Perlin; Strobel (2008) discuss deaf education. Chaves (2011) e Odete Fernando (2015) discuss games in mathematics teaching for deaf people. The results indicate that the inclusion of deaf students in this school environment are an element that deserves reflection because there are implicitly (actions by specialized school in what they placed the students with disabilities in the same classroom. In relation to playful in mathematics teaching, it was not possible seeing in the context of the investigated class. One of the factors reflects on the initial formation of the teacher because she was not properly trained to deal with such questions.